No. 6. Volume 7 - Asano, Atsuko, 1954- (Kodansha Comics, 2014)
For Shion, an elite student in city No. 6, life is carefully choreographed. School, study and occasional visits with his friend Safu are the order of the day. One fateful day however he takes a misstep, sheltering an injured boy from a typhoon. But this boy is a fugitive living outside the tapestry of control of the city.